EFFECT OF TAR AND CHITOSAN COATING ON PHYSICAL AND MECHANICAL PROPERTIES AND TECHNICAL LIFETIME OF PINEAPPLE LEAF FIBER ROPE IN A FRESHWATER ENVIRONMENT - Mokhamad Dahri Iskandar; Didin Komarudin; Vita Rumanti Kurniawati; Yopi Novita; Muhamad Zildan Sukmana; Iftitah Aura Azzahra; Kemal Fasya (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
Widespread use of synthetic materials in fishing gear has raised serious environmental concerns due to their non-biodegradable nature. Pineapple leaf fiber is a promising biodegradable material that can be used as a base for ropes in environmentally friendly fishing gear. This study aimed to analyze the physical and mechanical properties of PALF rope, particularly breaking strength and elongation, with surface treatments using tar and chitosan. The methods included specimen preparation, coating, freshwater immersion, and mechanical testing following SNI ISO 1805:2010. The results showed that chitosan coating improved breaking strength by 18.78% and elongation by 25.56% compared to the control. Coating treatments also affected the stress values, with the most significant reduction observed in tar-coated samples (57.89%). Immersion tests over five weeks indicated a decline in tensile strength and elasticity, with the control group showing the highest coefficient of determination (R² = 0.9145). Although chitosan-coated ropes degraded more quickly in terms of tensile strength, they maintained elongation capacity up to week 12. These findings suggest that chitosan-coated PALF ropes have strong potential as a biodegradable material for sustainable fishing gear. Key words: breaking strength, elongation, environmentally friendly fishing gear, pineapple leaf fiber